THE RECOMMENDATIONS FOR POLICY: STRATEGY MODEL FOR SURVIVAL ADAPTATION IN THE NEW NORMAL ERA OF ENTRERENEURS IN NAKHON NAYOK PROVINCE - เจียมวิจิตร, นัชส์ณภัทร์ (RMUTT Global Business and Economics Review, 2021)
This research aimed to study the characteristics of business, environmental factors, network factor and innovation factor affecting the survival in the new normal era of entrepreneurs in Nakhon Nayok Province, to study the patterns of strategies for survival adaptation in the new normal era of entrepreneurs in Nakhon Nayok Province and to suggest policy forms adaptation strategies for survival in the new normal era of entrepreneurs in Nakhon Nayok Province. The researcher did a mixed research by using qualitative research with in-depth interviews from those involved in policy 15 entrepreneurs in Nakhon Nayok Province followed by quantitative research from the collection of questionnaires of a group of entrepreneurs dealing with the production of goods group of companies related to services / travel and a group of retail entrepreneurs of 400 people. When analyzed, it was found that characteristics of the business, environmental factors, network factor and innovation factor affecting the survival of entrepreneurs in Nakhon Nayok Province Statistically significant at a level of 0.05. For a guideline for policy recommendations for the survival adaptation of entrepreneurs in Nakhon Nayok Province using matrix town can be defined as a strategy that consists of proactive strategies include marketing strategies on the social media space, a modified strategy is to build a network of entrepreneurs, preventive strategies, including modernization of work processes, and passive strategies such as promoting technology education for entrepreneurs.